2012
DOI: 10.1242/jcs.104083
|View full text |Cite
|
Sign up to set email alerts
|

Nm23-H1 regulates contact inhibition of locomotion which is affected by ephrin-B1

Abstract: SummaryContact inhibition of locomotion (CIL) is the process by which cells stop the continual migration in the same direction after collision with another cell. Highly invasive malignant cells exhibit diminished CIL when they contact stromal cells, which allows invasion of the tissue by tumors. We show that Nm23-H1 is essential for the suppression of Rac1 through inactivation of Tiam1 at the sites of cell-cell contact, which plays a pivotal role in CIL. U87MG cells show CIL when they contact normal glia. In s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 41 publications
1
30
1
Order By: Relevance
“…In many cases, homophilic binding between cadherin receptors on adjacent cells underlies the polarity signal, although the specific cadherin isoform and downstream signalling pathways involved are perhaps context-specific. Moreover, binding of ephrin ligands to cognate Eph receptors has been shown to underlie CIL in several cell types, including neural crest cells and prostate cancer cells [6,15,40]. Despite these inroads in understanding that highlight which molecules might be involved in the process, no study to date has quantitatively described the probabilistic nature of CIL, its relative strength, and its dependence on context.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, homophilic binding between cadherin receptors on adjacent cells underlies the polarity signal, although the specific cadherin isoform and downstream signalling pathways involved are perhaps context-specific. Moreover, binding of ephrin ligands to cognate Eph receptors has been shown to underlie CIL in several cell types, including neural crest cells and prostate cancer cells [6,15,40]. Despite these inroads in understanding that highlight which molecules might be involved in the process, no study to date has quantitatively described the probabilistic nature of CIL, its relative strength, and its dependence on context.…”
Section: Discussionmentioning
confidence: 99%
“…33 The metastasis suppressor activity of Nme1 has been demonstrated in many cancers except leukemias, lymphomas, and neuroblastoma. 34,35 Multiple aspects of metastasis have been implicated in Nme1 suppression, including cell adhesion, [36][37][38] motility and signaling, [39][40][41][42][43][44][45] and proteolysis. 46 As discussed by Kaetzel et al, 38 Nme1 promotes genomic stability in melanoma through direct interactions with at least two DNA repair pathways, nucleotide excision repair and doublestrand break repair.…”
Section: Ndpk and Tumor Metastasis Suppressionmentioning
confidence: 99%
“…Surprisingly, no single set of pathways has been shown to be Nme1-dependent. Rather, a bewildering host of adhesion molecules (Boissan et al 2010;Fournier et al 2002;Kaetzel et al 2014), motility factors, signaling pathways (Hartsough et al 2002;Masoudi et al 2013;Murakami et al 2008;Otero 1997;Otsuki et al 2001;Roymans et al 2000;Seong et al 2007;Tanaka et al 2012;You et al 2014), proteolytic events (Khan et al 2001), EMT hallmarks (Zhao et al 2013), and other transcriptional programs (Horak et al 2007) have been functionally linked to Nme1. A new, important finding showed that lysosomal cysteine cathepsins degraded Nme1 proteins under the direction of C-Abl and Arg, limiting invasiveness (Fiore et al 2014).…”
Section: Nme1 As Metastasis Suppressormentioning
confidence: 99%